D3‐Creatine dilution and the importance of accuracy in the assessment of skeletal muscle mass. Issue 1 (21st March 2019) - Evans, William J.; Hellerstein, Marc; Orwoll, Eric; Cummings, Steve; Cawthon, Peggy M.
Abstract: Sarcopenia has been described as the age‐associated decrease in skeletal muscle mass. However, virtually every study of sarcopenia has measured lean body mass (LBM) or fat free mass (FFM) rather than muscle mass, specifically. In a number of published sarcopenia studies, LBM or FFM is referred to as muscle mass, leading to an incorrect assumption that measuring LBM or FFM is an accurate measure of muscle mass. As a result, the data on the effects of changes in LBM or FFM in older populations on outcomes such as functional capacity, disability, and risk of injurious falls have been inconsistent resulting in the conclusion that muscle mass is only weakly related to these outcomes. We review and describe the assumptions for the most commonly used measurements of body composition. Dual‐energy X‐ray absorptiometry (DXA) has become an increasingly common tool for the assessment of LBM or FFM and appendicular lean mass as a surrogate, but inaccurate, measurement of muscle mass. Other previously used methods (total body water, bioelectric impedance, and imaging) also have significant limitations. D3 ‐Creatine (D3 ‐Cr) dilution provides a direct and accurate measurement of creatine pool size and skeletal muscle mass. In a recent study in older men (MrOS cohort), D3 ‐Cr muscle mass was associated with functional capacity and risk of injurious falls and disability, while assessments of LBM or appendicular lean mass by DXA were only weakly or not associated with these outcomes. Inaccurate measurements of muscle mass by DXA and other methods have led to inconsistent results and potentially erroneous conclusions about the importance of skeletal muscle mass in health and disease. The assessment of skeletal muscle mass using the D3 ‐Cr dilution method in prospective cohort studies may reveal sarcopenia as a powerful risk factor for late life disability and chronic disease.